Artificial insemination in pig: Technology for producing quality piglets in Nagaland - Singh, Mahak; Patra, M K; Mollie, R Talimoa; Ngullie, Ebibeni; Rajkhowa, D J (Indian Farming, 2019)
Pig rearing is an integral part of traditional Naga life. The rural tribal population comprises about 80% of the state who are mostly engaged in agriculture and some form of animal husbandry. Pig is most important livestock which plays an integral role in improving the economic status of the tribal and weaker section of the Nagaland. Pig alone accounts for 55.38% of the total livestock population in Nagaland, but still a wide gap exists between the demand and availability of pork mainly due to traditional production system. Nagaland is the highest pork consuming state on per capita basis. The swine population of Nagaland stood at 0.698 million at the last estimate (2013) which is an immediate increase from 0.504 million (2012). Out of this, 75.59% are exotic or mixed while 24.41% are indigenous breeds. However due to indiscriminate breeding the genetic potential of the swine population has become unpredictable and there arises an urgent need to introduce and supply improved germplasm in the state.